Alkol-madde kullanan adolesanlara verilen cinsel-üreme sağlığı eğitiminin etkinliği - Ataman, Hacer (My University, 2014)
Araştırma, alkol-madde kullanan adolesanlara verilen cinsel-üreme sağlığı eğitiminin (CS/ ÜS) etkinliğini değerlendirmek amacıyla deneysel olarak yapılmıştır. Araştırmanın evrenini, Çocuk ve Ergen Madde Bağımlılığı Araştırma, Tedavi ve Eğitim Merkezi’nde yatarak tedavi görmekte olan alkol-madde kullanan adolesanlar oluşturmaktadır. Adolesanlar 1. grup (kontrol), 2. grup (bir defa eğitim verilen) ve 3. grup (iki defa eğitim verilen) olarak gruplanmış; gruplara 20 erkek, 10 kız adolesan alınmıştır. Veriler, Adolesanları Tanıtıcı ve Cinsel Sağlık-Üreme Sağlığı İle İlgili Bilgi Formu ve Cinsel Sağlık-Üreme Sağlığı Eğitim Modüllerine İlişkin Bilgi Formu ile Eylül 2011-Aralık 2012 tarihleri arasında toplanmıştır. CS/ ÜS eğitimine ilişkin grupların test toplam puanları kendi içinde incelendiğinde; 2. ve 3. grubun puanları arasında istatistiksel olarak ileri düzeyde anlamlı değişim görülmüştür (p<0.01). Ön test toplam puana göre son test toplam puanlarındaki değişim grup içinde incelendiğinde; 3. grubun puanındaki artış (34.57±16.33), 1. (2.73±10.65) ve 2. grubunkinden (20.23±12.09) istatistiksel olarak ileri düzeyde anlamlı şekilde yüksektir (p<0.01). Eğitim modüllerine ilişkin grupların test puanları kendi içinde incelendiğinde; aile planlamasında yalnız 3., diğer modüllerde ise 2. ve 3. grubun puanları arasında istatistiksel olarak anlamlı/ ileri düzeyde anlamlı fark saptanmıştır (p<0.05, p<0.01). Eğitim modüllerine ilişkin test puanları gruplararasında incelendiğinde; güvenli cinsellik hariç diğer modüllerde ön test puanları arasında istatistiksel olarak anlamlı fark saptanmamışken (p>0.05); 1., 2. ve son test puanları arasında ileri düzeyde anlamlı fark saptanmıştır (p<0.01). Modüllerin etkinliğine bakıldığında cinsel yolla bulaşan hastalıklar 1., üreme sistemi, cinsel istismar-şiddet 2., güvenli cinsellik, aile planlaması 3. sıradadır. Alkol-madde kullanan adolesanlara riskli cinsel davranışların önlenmesine yönelik, CS/ ÜS eğitimi tekrar edilerek verilmelidir. Adolesan, alkol, cinsel sağlık, madde, üreme sağlığı

Effectiveness of the Sexual Health-Reproductive Health (SH/ RH) Education Given to Adolescents Who Consume Alcohol or Illicit Substances The research was conducted experimentally to evaluate the effectiveness of the sexual health-reproductive health (SH/ RH) education given to adolescents who consume alcohol or illicit substances. The population was adolescents who consumed alcohol and substances and were inpatients at the Child and Adolescent Substance Addiction Research, Treatment and Education Centre. The adolescents were grouped into the following 3 groups:group 1. (control group), group 2. (those who have received training once) and group 3. (those who have received training twice), each having 20 male and 10 female adolescents. Data was collected between September 2011-December 2012 using the forms Self-Introduction and Information on Sexual Health-Reproductive Health and Information on Sexual Health-Reproductive Health Education Modules. Upon studying the total SH/ RH test scores of the groups individually, a statistically significant difference was observed in the scores of groups 2. and 3. (p<0.01). Upon studying the change in the posttest scores from the pretest ones for each group individually, the increase in the scores of group 3 (34.57±16.33) was observed to have a statistically highly significant difference from those of groups 1 (2.73±10.65) and 2 (20.23±12.09) (p<0.01). Upon studying the individual groups’ test scores on education modules, a statistically significant/ highly significant difference was observed for family planning in group 3. and for all other modules in both group 2. and group 3. (p<0.05, p<0.01). Upon comparing the education test scores between groups; -although there was no statistically significant difference between the groups in pretest scores for any of the modules with the exception of safe sexuality (p>0.05)- a statistically highly significant difference was observed between the 1st, 2nd and final test scores (p<0.01). As for the effectiveness of the modules, they rank as follows: 1. sexually transmitted diseases, 2. the reproductive system and sexual abuse/ violence, 3. safe sexuality and family planning. Adolescents who abuse alcohol or substances should be given SH/ RH education in a repetitive manner for prevention of risky sexual behaviour. Key Words: Adolescent, alcohol, sexual health, substance, reproductive health
Keywords: Alkol Bağımlılığı; Cinsel Sağlık; Hemşirleik_Kadın Hastalıkları; Kadın Hastalıkları ve Doğum; Madde Bağımlılığı; Sağlık; Üreme Sağlığı